On analysis of nonlinear dynamical systems via methods connected with $$\lambda $$ λ -symmetry - Gülden Gün, Polat; Teoman, Özer (Springer Science and Business Media LLC, 2016)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Liénard equations; nonlinear dynamical systems; linearization; Lie point symmetry; Generic properties, structural stability of dynamical systems; \(\lambda \)-symmetry; local and nonlocal transformations; extended Prelle-Singer method; Linearizations